Modos de viver, religião, cultura militar : os Húngaros e o seu território nas fontes muçulmanas da Península Ibérica, entre os séculos IX e XII - Igaz, Levente (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Referred to for the fi rst time in written sources in the West in the second half of the 9th century, the Hungarian tribes must have arrived to the region of the Carpathian Basin around 894-895. Until 902 they occupied a vast territory and, at the same time, started military expeditions into various European regions. These incursions reached, at times, distant lands in the continent and, therefore, from an early date, they came to the attention of very different authors of Medieval Europe (Byzantines, Germans, Italians, Muslims). This article intends to make available to a Portuguese-speaking audience a selection of the most representative texts by Muslim authors of Hispanic origin who wrote about the ancient Hungarians between the 9th and 12th centuries: it is hoped, thereby, to contribute to a widening of the context of those studies which discuss Iberian-Hungarian relations during the Medieval period.